(untitled) (Global Media Journal - German Edition, 2022)
Over the last couple of decades, queer theory has stimulated researchers in different disciplines to fundamentally question central concepts around identity, body, gender, sexuality, and belonging. Scholarship on diasporic media, however, has been slow to engage with queer theory’s contributions; much research still works with definitions of diaspora based upon simple notions such as ‘ethnic belonging’ and fails to interrogate the hetero- and cisnormativities that structure phenomena such as mediascapes, border regimes, and migration discourses. After discussing some of the theoretical and methodological interventions that queer theory can bring to digital diaspora research, this article presents a case study to exemplify how queer theoretical discussions can be implemented in research. Madi Ancestors was initially planned as a festival in a theater building in Berlin to remember and celebrate Turkey’s queer idols, but was then forced by the COVID-19 pandemic to migrate from a physical space to a digital platform. My explorative analysis of this process demonstrates how media practices bring forth a sense of queer diasporic belonging both locally and transnationally. Drawing on rich data gathered through digital ethnography, intimate insider research, interviews, and ethno-mimesis, I show how queer theoretical examination of digital diaspora can detail new forms of belonging, intergenerational kinship, and the fragmentation of diasporic spaces through digital media.